2011
DOI: 10.1016/j.icarus.2010.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the secondary emission yield of salty ice dust grains

Abstract: Please cite this article as: Richterová, I., Němeček, Z., Pavlu, J., Beránek, M., Šafránková, J., Modeling the secondary emission yield of salty ice dust grains, Icarus (2010Icarus ( ), doi: 10.1016Icarus ( /j.icarus.2010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…For these samples, ı max and its corresponding energy, E 0max , were also calculated. In addition, literature values for graphite are shown for comparison [13,19,31]. Our results, e.g.…”
Section: Sey Of a Mlm And Graphitementioning
confidence: 57%
“…For these samples, ı max and its corresponding energy, E 0max , were also calculated. In addition, literature values for graphite are shown for comparison [13,19,31]. Our results, e.g.…”
Section: Sey Of a Mlm And Graphitementioning
confidence: 57%
“…The influence of porosity on electron-induced SEE was considered by Millet and Lafon [12]. There are also some numerical models of SEE from dust grains [24]. However all these approaches assume a smooth surface of the object.…”
Section: Introductionmentioning
confidence: 99%
“…When a σ T increase along the electron path is not omitted, electrons travel a shorter distance than that given by the mean-free path, λ(E). This effect is potentially important for samples containing light species and, thus, Richterová et al (2011b) suggested a model correction that was applied to ice grains. The present calculations follow this approach.…”
Section: Model Outlinementioning
confidence: 99%